Linear Combinations of the Volterra Dissipative Operator and Its Adjoint Operator - Gubreev, G. M.; Olefir, E. I.; Tarasenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the spectral properties of linear combinations of the Volterra dissipative operator and its adjoint operator in a separable Hilbert space.